An Analysis of Real, Self-Perceived, and Desired BMI: Is There a Need for Regular Screening to Correct Misperceptions and Motivate Weight Reduction? - Easton, Jonathan F.; Stephens, Christopher R.; Sicilia, Heriberto Román (Frontiers in Public Health, 2017)
We study the relationship among real, self-perceived and desired BMI in 21288 adults from the Mexican national health and nutrition survey 2012, analysing the effect of sex and diagnosis of obesity/overweight by a healthcare professional. Self-perceived and desired BMI are analysed via a figure rating scale question and compared to real BMI. Only 8.8% and 6.1% of the diagnosed and non-diagnosed obese, respectively, correctly identify themselves as such. For the obese, 20.2% of non-diagnosed and 12.7% of diagnosed perceive themselves as normal or underweight, while 49.1% and 37% of these are satisfied with their perceived BMI. Only 7.8% of the obese, whose real and perceived BMI coincide, have a desired BMI equal to their perceived one. In contrast, 43.2% of the obese whose perceived BMI is normal, have a desired BMI the same as their perceived one. Although the average desired body figure corresponds to the normal BMI range, misperceptions of BMI correlate strongly with the degree of satisfaction associated with perceived BMI, with larger misperceptions indicating a higher degree of satisfaction. Hypothesizing that the differences between real, perceived and desired weight are a motivator for weight change, one potential intervention could be the periodic assessment of real, perceived and desired BMI in order to correct misleading weight misperceptions that could potentially obstruct positive behavioural change.